GEOLOGY AND 3D STATIC RESERVOIR MODELLING OF SG FIELD, AIR BENAKAT FORMATION, SOUTH SUMATERA BASIN - Asriliana, Annisa
SG Field is a gas field located in the South Sumatera Basin, Jambi Sub-basin and covers an area of 5.8 x 3.8 km2. The objectives of this study are to determine SG Field’s geological setting, to generate static reservoir model, and to estimate initial hydrocarbon in place. The study is focused on three sandstone reservoirs in Air Benakat Formation which are Reservoir 2, Reservoir 3, and Reservoir 4. The dataset used in this study includes wireline log of 20 wells, 3D seismic data, and the report of core description data. The methods used in this study consist of four evaluation methods, which are: well data analysis by doing well-to-well correlation using sequence stratigraphy concept and petrophysical analysis; seismic data analysis by generating depth structure map and interpreting reservoir geometry; the integration of well data and seismic data; reservoir modelling by generating 3D structure model, generating petrophysiscal model, determining fluid contact, and estimating intial hydrocarbon in place. The results of these methods are the stratigraphy and structure of SG Field which are derived from integration of well data and seismic data, each reservoir interval is sandstone with varied thickness between 3 – 24 metre. Main structure of SG Field is an anticline associated with northwest – southeast trending strike-slip fault and northeast – southwest normal fault. The depositional facies of Reservoir 2, Reservoir 3 and Reservoir 4 is tidal chanel and tidal sand bar in estuarine system. The initial gas in place estimation of those reservoirs is 50.4 BSCF